Evolving Toolbox for Complex Project Management - Gorod, Alex; Hallo, Leonie; Ireland, Vernon; Gunawan, Indra (Complex and enterprise systems engineering., 2019)
This book enhances learning about complex project management principles and practices through the introduction and discussion of a portfolio of tools presented as an evolving toolbox. Throughout the book, industry practitioners examine the toolsets that are part of the toolbox to develop a broader understanding of complex project management challenges and the available tools to address them. This approach establishes a dynamic, structured platform for a comprehensive analysis and assessment of the modern, rapidly changing, multifaceted business environment to teach the next generation of project managers to successfully cope with the ever increasing complexity of the 21st century.